PELAYANAN DOKUMEN PAKET KEMATIAN MELALUI PROGRAM SEDUDO DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN NGANJUK PROVINSI JAWA TIMUR - Hutasoit, Imelda; Pribadi, Ari Samudro (Jurnal Konstituen, 2023)
Apart from various family needs, processing death documents in the form of a Death Certificate is very necessary so that the real condition of the population is described validly. However, the rate of ownership of population documents, especially in cases of death, only reached 32.70%. The aim of this research is to analyze death package document services through the SEDUDO program which is reviewed through 4 dimensions, namely efficiency, economy, fairness and effectiveness. The research method used in this research is Descriptive Qualitative. Data collection uses several methods, namely observation, interviews and documentation. The analysis technique is carried out using several stages, namely preparing the data, reading all the data, presenting the data, coding or organizing the data, analyzing the data, describing the data that has been analyzed, and making interpretations or drawing conclusions. In this research, the death package document service was not optimal because there were several problems, including facilities and infrastructure that were not optimal due to the presence of several employees who held concurrent jobs and some who did not comply with their duties and functions, lack of admin response in responding to complaints about the SEDUDO program, resulting in ownership Death package documents in Nganjuk Regency have never reached the perfect target. Several efforts have also been made, namely improving facilities and infrastructure, increasing the role of social media in outreach related to the SEDUDO program and increasing the role of RTs in reporting and registering the production of death package documents. The suggestions given are updating and implementing regulations, carrying out outreach, and improving the quality of human resources and existing facilities and infrastructure.